2016
DOI: 10.1016/j.jvs.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Temporary inferior vena cava filter indications, retrieval rates, and follow-up management at a multicenter tertiary care institution

Abstract: Given the established complications relating to long indwelling times and recent Food and Drug Administration guidelines, a multidisciplinary and systematic follow-up protocol needs to be implemented to optimize filter retrieval rates and to ensure exemplary quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Procedural codes were utilized to identify VCF placement; however, these codes are not specific to permanent or retrievable devices. As of 2006, retrievable devices made up about 85% of the VCF market in the United States, which likely increased to >90% since then 38, 39, 40, 41. Therefore, the retrieval estimates presented here are underestimated.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Procedural codes were utilized to identify VCF placement; however, these codes are not specific to permanent or retrievable devices. As of 2006, retrievable devices made up about 85% of the VCF market in the United States, which likely increased to >90% since then 38, 39, 40, 41. Therefore, the retrieval estimates presented here are underestimated.…”
Section: Discussionmentioning
confidence: 84%
“…As of 2006, retrievable devices made up about 85% of the VCF market in the United States, which likely increased to >90% since then. [38][39][40][41] Therefore, the retrieval estimates presented here are underestimated. Assuming that 10% to 20% of all VCFs used are permanent and thus cannot be retrieved, this would make our estimated retrieval 26% to 30%, making this corrected estimate near previous estimates of national retrieval rates of 30%.…”
Section: Limitationsmentioning
confidence: 86%
“…Failure to retrieve of IVC filter could be caused by several reasons including, patients being lost to follow-up, considerable thrombus within the filter, substantial filter tilt, embedded filter tip, embedded filter struts, strut perforation, and filter fracture. Multidisciplinary and systematic follow-up protocol, dedicated IVC filter clinic and proactive attitude previously shown to optimize filter retrieval rates in addition to optimization of resource allocation, and increased patient safety (6,7,35).…”
Section: Discussionmentioning
confidence: 99%
“…While the rate of filter implantation has more than doubled within the past several years, with a continuously increasing trend, the retrieval rates remain quite low, with a mean retrieval rate of 34%; figures as low as 8.5% are also reported. Thus the majority of retrievable IVC filters are not removed (4)(5)(6)(7). One prospective randomized trial…”
Section: Introductionmentioning
confidence: 99%
“…56 Several studies have shown that dedicated, systematic follow-up programs improve both the rate and timeliness of filter retrieval, [57][58][59][60] with studies demonstrating a 6.7-to 14fold increase in retrieval rates following initiation of such a program. 61,62 Showcasing the importance of programs such as these has been the recent large increase in litigation related to complications resulting from IVC filters.…”
Section: Retrieval Rates Of Inferior Vena Cava Filtersmentioning
confidence: 99%